A relationship marketing theory on factors influencing intention to contribute to waqf in higher education institutions : evidence from IIUM - Alimova, Shakhnoza (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
This research aims to examine factors that influence the intention to contribute to waqf in higher education institutions in Malaysia based on relationship marketing theory. Waqf plays very significant role in Muslim world since many centuries, and it has been paid more attention in Malaysia recently. Increasing interest on capitalizing waqf to support higher education institutions to ease financial difficulties become main concern for researchers. Therefore, there is an increasing interest of research to study waqf particular higher education context to ease financial difficulties. In this study, data has been collected from 260 academic and non-academic staffs of Internationals Islamic University Malaysia in order to identify factors affecting intention to contribute to waqf. The conceptual framework in this study is based on relationship marketing theory, which includes satisfaction, commitment, trust, religiosity and income. Regression analysis is conducted in order to identify relationship between independent and dependent variables. The findings of this study show the significance of satisfaction, trust and income on intention to contribute to waqf. However, commitment and religiosity have non-significant relationship with intention to contribute to waqf. This research will help practitioners to understand how intention contribute to waqf fund in higher education institutions can be further improved.